2020
DOI: 10.1016/j.ejca.2020.05.028
|View full text |Cite
|
Sign up to set email alerts
|

High mortality rate in cancer patients with symptoms of COVID-19 with or without detectable SARS-COV-2 on RT-PCR

Abstract: Background: Cancer patients presenting with COVID-19 have a high risk of death. In this work, predictive factors for survival in cancer patients with suspected SARS-COV-2 infection were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
5
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(155 citation statements)
references
References 27 publications
5
140
5
4
Order By: Relevance
“…After a full-text review, 23 articles were excluded due to the violation of inclusion criteria and the remaining 17 articles were eligible for inclusion in the current analysis. 3,13,15,16,[25][26][27][28][29][30][31][32][33][34][35][36][37]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After a full-text review, 23 articles were excluded due to the violation of inclusion criteria and the remaining 17 articles were eligible for inclusion in the current analysis. 3,13,15,16,[25][26][27][28][29][30][31][32][33][34][35][36][37]…”
Section: Resultsmentioning
confidence: 99%
“…3,13,15,16,[25][26][27][28][29][30][31][32][33][34][35][36][37] Detailed clinical characteristics of the study patients are reported in Table 1. Seven studies were performed in China, 3,9,13,15,25,26,32 five in the USA, 16,[27][28][29][30] two in Spain, 33,37 one in France, 36 and the other two in Italy. 31,35 Four of the included studies reported data on patients who diagnosis with COVID-19 while they received anti-cancer therapy.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, patients with lymphopenia 11 , 41 , 42 , 43 and granulocytosis 33 , 44 were reported to be at an increased risk for severe or fatal COVID-19. Further factors with possible impact on COVID-19 course and outcome are listed in Table 2 .…”
Section: Risk Factorsmentioning
confidence: 99%
“…Coronavirus disease 2019 (COVID-19), resulting from severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) appears to affect children less severely than adults with majority of benign forms and asymptomatic cases [1]. High mortality rate have been recently reported in adult patients with cancer [2,3]. Data is still limited in children with cancer while some reports suggested that they may be quite safe regarding the infection [4][5][6].…”
Section: Introductionmentioning
confidence: 99%